The Terror Campaign of Boko Haram: Its Transformation and Challenges to Nigeria’s Security - Bello, Mukhtar (Manunggal Halim Jaya, 2021)
This paper is geared toward analyzing the patterns and dynamics of the Boko Haram attacks and the challenges they caused to the country's security. The report uses the assumptions of the instrumental approach, which states that the purpose of terrorism is to bring about insecurity in an actor's environment. The pattern of terrorism follows an action-reaction process. Thereby it responds to what Government does. It also utilizes the data collected from secondary sources and qualitatively analyses it. The paper discovered that Boko Haram, a proscribed international terrorist organization, is continuously posing serious security challenges to Nigeria that have resulted in the loss of over 30.000 lives and the destruction of public and private properties worth billions of US dollars. The group has committed itself to asymmetric warfare. Since its re-emergence, it had tried to mimic and adopt the tactics and strategies of global Salafist movements, which manifested in armed assaults, bombings, and abductions. The paper recommended that a comprehensive approach be adopted that would take care of both kinetic and non-kinetic measures to end the menace of terrorism in Nigeria. Training and retraining of security personnel on asymmetric warfare are required to balance the increasing adaptability of the terrorists.